Effect of Oral Methylphenidate on the Experimental Epileptiform Activity in Male Rats - Yousef Panahi; Davood Kiani Fard; Fatemeh Feyzi (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk, 2020)
Background and Aim: The purpose of this study was to investigate the stimulatory and protective effects of Methylphenidate (MPD) on the experimental epilepsy induced by intraperitoneal injection of Pentylenetetrazole (PTZ) in adult male rats. Methods & Materials: In this study, 15 male rats (weight, 200-250 gr) dividied into one control group (n=5) received normal saline and two treatment groups; the first group (n=5) received MPD with a dose of 2.5 mg/kg and the second group (n=5) received MPD with a dose of 5 mg/kg by gavage. After anesthesia with ketamine-xylazin combination and animal skull surgery, the recorded electrodes were inserted into the cranium in the stratum striatum layer of the CA1 region of the hippocampus, and epileptic activity was induced by intraperitoneal injection of PTZ (80 mg/kg) and the epileptiform activity was evaluated in terms of the number of spikes per time unit and their amplitudes by eTrace software. Ethical Considerations: This study with an ethics code of FVMT.REC.1397.67 was approved by the Research Ethics Committee of the Faculty of Veterinary Medicine at University of Tabriz. Results: Oral MPD at 2.5 and 5 mg/kg doses increased the number of spikes up to 576 and 613, respectively, compared to the control group (330 spikes), which were statistically significant. Amplitude of PTZ-induced epileptic activity after treatment with 2.5 and 5 mg/kg MPD reached 1254 and 1085 respectively compared to control group (1051), which were not statistically significant. Conclusion: The doses of oral MPD used in this study potentiate seizure activity. Therefore, the use of this drug in people with a background of seizure or suffering from some types of seizure should be cautious, and the evaluation of its effect in these patients need further studies.